Assessing Farmers’ Prefrences in using Water Resources in Varamin Plain, Iran A Discrete Choice Experiment Technique - Hojatolah Shayeganfard; Mohsen Mehrara (پژوهشهای اقتصادی)
Aim and Introduction Tehran province and its southeastern area (Varamin Plain) is a clear example of the dire situation in the country in terms of water scarcity. While the average rainfall in this area has always been declining in recent years, agricultural practice in this area is facing a difficult situation due to digging unauthorized wells, lack of clear water rights for the upstream dams, as well as transfering part of the wastewater from Tehran metropolis. In the past periods, the agricultural water of Varamin plain was supplied from atmospheric precipitation, water rights of upstream rivers and canals. Due to frequent droughts and other unnatural and human factors, these resources have been replaced by other sources of supply such as agricultural wells, water rights of upstream dams and Tehran urban sewage effluents. This form of water supply during planting and farming seasons, have created many problems for the farmers in Varamin Plain. In this article, while identifying these problems, impact assessment of the most important variables on Varamini farmers' preferences in using water resources extracted from irrigation canals are discussed by applying the discrete choice test method. Methodology Considering the widespread use of the discrete choice test technique in extracting the preferences of goods and services for which there is no market, or the market is incomplete, in this research, in order to value and extract the willingness to pay for non-market variables (water quality, water release rights of dams and canals, the quality status of water canals and how to monitor the water flow) by considering the variable "water price" as the normalizing monetary variable, the discrete choice test technique has been used. To achieve this goal, four steps; Identification of variables and their levels, design of selection sets, distribution of questionnaires and data collection and finally implementation of statistical analysis have been done. Findings The signs of the estimated coefficients show that any reduction in agricultural water price, improved water quality, tightened water source monitoring, guaranteed water rights released from the dams and canals, improved and expanded water canals will increase the level of utility of Varamini farmers. In the context of farmers' willingness to pay (by including agricultural water price variable as a normalizing monetary variable), the research findings showed that the variable "water rights status released from dams and canals" is the most important one in the preferences of the respondents (farmers) who are willing to pay a higher price of 58% of water in exchange for guaranteeing the supply and receipt of water during the low rainfall seasons of the year. This shows the vulnerability of farmers and agricultural products cultivated in Varamin Plain in the face of water scarcity and drought crisis. Discussion and Conclusion By including the agricultural price water rate variable as a normalizing monetary variable), the findings of the research showed that "the status of water rights created by dams and canals" variable is the most important in the preferences of the respondents (farmers), as they are willing to spend the most for guaranteeing the supply and receipt of water in the low rainfall seasons of the year (paying 58% of the higher water price to guarantee water rights in the planting and harvesting seasons). On the other hand, "monitoring status of water mains" variable has the least importance in the preferences of the respondents (farmers) in such a way that they are willing to pay only 11% more for intensifying monitoring of water mains. On the other hand, the calculations related to the probability of choosing the levels of the variables showed: a) the probability of choosing the current price of water is equal to 55%. b) the probability of choosing higher quality water is 63%. c) the probability of choosing a centralized government supervision on the performance of waterworks is equal to 57%. d) The probability of trying to get enough water in the summer seasons (hot seasons) is equal to 81%. f) The probability of paying attention to the repair and expansion of the canals is equal to 60%. In addition to that, in the context of providing policy recommendations, it is suggested to pay serious attention to the issue of agricultural water in the Varamin Plain. Establishing a chemical treatment plant, and improving irrigation canals, are highly recommended since agricultural produce of this plain are considered as one of the main sources of food supply for Tehran metropolis. Otherwise, it can potentially cause detrimental damage to the health of Tehran citizens due to heavy metal penetration into agricultural produce in the long term. Any form of negligence will make the fertile lands of the region barren and uncultivable due to the accumulation of heavy metals in the soil